Gadget dan Perkembangan Sosial Anak Usia Dini - Delpima Suhita; Melinedri Melinedri; Tika Meldina; Yulya Muharmi; Nella Novita (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
Gadgets are a result of the development of information technology. Gadgets are multi-functional media that are not only used as a medium of communication but also as a medium of information and recreation. With this small device, a wireless gadget can be carried and used anywhere. Not a few people are addicted to gadgets, including children. This dependence can be caused because gadgets help in work, it can also be due to dependency due to hobbies so that it becomes